Reconciling the North: Transit Pipelines and the Pursuit of Self-Sufficient Self-Government in the Yukon - Wilson, Nicholas J. (Journal of Aboriginal Economic Development, 2018)
The research investigates how the responsibilities of Self-Governing Yukon First Nations (SGYFNs) regarding Settlement Land under the Umbrella Final Agreement, 1993, can be used to advance pipeline projects on Indigenous land title. In doing so, it challenges the contemporary notion of the Westphalian state system that has come to define the modern nation-state entity. Accordingly, the investigation employs contemporary border theory to examine how the responsibilities and obligations of SGYFNs, the Government of Yukon, and the Government of Canada can solve Aboriginal boundary issues to develop a sustainable Arctic economy in the 21st century, which is on the verge of unprecedented opportunity. As such, it takes transnational pipeline projects in developing countries as the basis of a trans-territorial model within the Canadian context, before concluding that it is equitable, lawful, and fair to provide incentives to reluctant Yukon First Nations to consent to pipeline development projects on Settlement Land.